Performance analysis of PSO MPPT for photovoltaic (PV) system during irradiance changes / Kharismi Burhanudin - Burhanudin, Kharismi (2018)
Maximum power point tracking have been widely used to track maximum power from the PV panel. The study focus on extracting maximum power from the PV panel based on the change in solar irradiance absorbed by the PV panel. In order to validate the workability of the proposed technique, development of the MPPT test-rig device is implemented consisting proposed MPPT method. The MPPT method applied to track maximum power from PV panel is particle swarm optimization (PSO). Particle swarm optimization is soft computing methods which follow the bird swarm to track maximum power from PV panel. The process continues repeatedly to track maximum power depending on the swarmsize of the MPPT algorithm. In order to validate this technique simulation was conducted using MATLAB SIMULINK software in order to observe and identify the output power extracted from the PV panel. SIMULINK prove to be efficient due to the features of the simulation software that allow observation of the PV power collected from the PV panel. In order to verify the proposed technique, output from the PV panel is also compared with the output power collected using perturb and observe (PNO) and incremental conductance (IC) MPPT method. The hardware was tested using PV simulator (Chroma programmable 62000H DC power supply) to identify the output power extracted from the PV panel for each irradiance value.